Physiotherapeutic interventions in burn patients in the Intensive Care Unit: literature review - Silva, Deyse Santos da (2021)
Introduction: Burns are injuries that can be superficial, affecting only the skin, as well as compromising layers of the skin being able to reach the bone. Objective: The main objective of the following review is to show the importance and relevance of the physiotherapist in the treatment of burn patients in the hospital environment. Methods: The following article is the following article is a literature review systematic considering articles from 2012 to 2021 in the databases: Latin American and Caribbean Literature on Health Sciences (LILACS), US National Institute of  Health(PubMed), Scientific Electronic Library Online (SciElo). Results and discussion: The physiotherapy professional is inserted in an intensive care unit to compose a multidisciplinary team in order to provide benefits to all patients there with individualized treatment plant s. Conclusion: Therefore, in order to return functionality to the patient, either early conduct to remove him from the bed for the purpose of inhabit deformities, contractures and associated pathologies.